Applying Hassle Lines Strategy to Improve the Students’ Speaking Skill - Kholid, Mohammad Ridho; Noviyandi, Andi (Attractive : Innovative Education Journal, 2020)
This article was to improve the students’ speaking skill at the eleventh grade at sate senior high school 10 Bandar Lampung through Hassle Lines Strategy. Classroom Action Research was used in this method, with the sample of twenty six students that consist of 8 male and 18 female.In cycle of Hassle Lines Strategy, 81% the students prepare the conversation actively, 92% students practice orally, 65% students can mention the body language, and 85% students share to the teacher. From questionnaire, the researcher got the data Hassle Lines Strategy implementing was 91% of student agree and 9% of student disagree, the positive respond accomplished. From the test, 81% of students passed the KKM in post Hassle Lines Strategy implementing. Keywords: Hassle Lines Strategy, Speaking Skills, Learning Strategy